Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1029/2018jd030140
|View full text |Cite
|
Sign up to set email alerts
|

Regional Snow Parameters Estimation for Large‐Domain Hydrological Applications in the Western United States

Abstract: In snow‐dominated regions, a key source of uncertainty in hydrologic prediction and forecasting is the magnitude and distribution of snow water equivalent (SWE). With ensemble simulations, this work demonstrates that SWE variability across the mountain ranges of the western United States (represented by 246 Snow Telemetry stations) can largely be captured at the daily time scale by a simple mass and energy‐balance snow model with four physically reasonable parameters—three snow albedo parameters and one snow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 96 publications
1
77
0
Order By: Relevance
“… c.SNOTEL In Situ SWE Data As a further evaluation, we compared the modeled SWE with the SNOTEL (Serreze et al, 1999) data, which are point scale in situ SWE observations collected by the Natural Resources Conservation Service (NRCS) in the western United States, including Alaska. Pacific Northwest National Laboratory provided BCQC SNOTEL data (Sun et al, 2019; Yan et al, 2018), consisting of bias‐corrected and quality‐controlled daily SWE data up through 30 September 2018 for 829 active stations located in the western United States and Alaska. The data are available from the Pacific Northwest National Laboratory (https://dhsvm.pnnl.gov/bcqc_snotel_data.stm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… c.SNOTEL In Situ SWE Data As a further evaluation, we compared the modeled SWE with the SNOTEL (Serreze et al, 1999) data, which are point scale in situ SWE observations collected by the Natural Resources Conservation Service (NRCS) in the western United States, including Alaska. Pacific Northwest National Laboratory provided BCQC SNOTEL data (Sun et al, 2019; Yan et al, 2018), consisting of bias‐corrected and quality‐controlled daily SWE data up through 30 September 2018 for 829 active stations located in the western United States and Alaska. The data are available from the Pacific Northwest National Laboratory (https://dhsvm.pnnl.gov/bcqc_snotel_data.stm).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we conducted four sensitivity simulations using the LSM for Chinese Academy of Sciences (CAS‐LSM) (Xie et al, 2018) driven by different atmospheric forcing data sets, that is, GSWP3, CRU‐NCEP, WFD/WFDEI, and Princeton. We assessed the modeled SCF, SWE, and SDP using a set of observations, including the Moderate Resolution Imaging Spectroradiometer (MODIS)‐based SCF product (Hall & Riggs, 2015), the Advanced Microwave Scanning Radiometer for EOS (AMSR‐E)‐derived SWE product (Tedesco et al, 2004), SWE from the Snowpack Telemetry (SNOTEL) network (Serreze et al, 1999; Sun et al, 2019; Yan et al, 2018), SDP from the China Meteorological Administration (CMA), and SDP from the University of Arizona (UA; Broxton et al, 2019; Zeng et al, 2018). In addition to the detailed evaluation of our modeling results, our analysis allowed for a comparison between the four forcing data sets and the sensitivities of the simulated snow evolution to the forcing uncertainties in different snow climates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extend NG-IDF curves in time and space beyond the limited coverage of the SNOTEL data, the authors (Sun et al, 2019) developed and validated regionally coherent DHSVM snow parameters. By using the BCQC SNOTEL data at 246 sites over the WUS, the authors (Sun et al, 2019) performed a generalized sensitivity test for the DHSVM snow model and identified sensitive snow parameters that control daily SWE evolution under diverse climate regimes. Regional parameters were then developed for these sensitive snow parameters for eight ecoregions (CEC, 2009) characterized by a distinct hydroclimatic regime across the WUS.…”
Section: Physics-based Hydrologic Modeling: Extending and Validating mentioning
confidence: 99%
“…However, parameter values are often abstract even in physically-based models, observations may be lacking, or ones found in literature may be inappropriate. For spatially distributed snow model applications, especially when applied in very heterogeneous environments or at large scales, the problem of suitable spatial parameter aggregation arises (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%